Female Students’ Knowledge Regarding the Importance of Breast Self-Examination: A Cross-Sectional Study: Pengetahuan Mahasiswi Mengenai Pentingnya Pemeriksaan Payudara Sendiri (SADARI): Sebuah Studi Cross-Sectional - Hazim N. Waheeb (Universitas Muhammadiyah Sidoarjo, 2024)
Background: The most crucial screening technique for the early identification and diagnosis of breast cancer is breast self-examination (BSE), in which women examine their breasts regularly to look for any abnormalities and seek immediate medical assistance. Objectives: To identify female students’ knowledge regarding the importance of breast self-examination. Methods: To evaluate female students' understanding of the significance and technique of breast self-examination, a descriptive cross-sectional study was carried out. The study began on November 1st, 2023, and ended on March 30th, 2024. 200 female students made up the non-probability (purposeful) sample, and the study tool was a questionnaire. Following a thorough analysis of relevant studies and the body of existing literature, the questionnaire was adopted. Data collection began on February 4, 2024, and ended on February 15, 2024. The researcher then explained the study and its goals to the study sample, obtained verbal consent from the female students, and conducted direct interviews with the students to answer the questionnaire, which took roughly five to ten minutes. Results: The current study's researchers found that the majority of the sample was unmarried, that the age range of 20 to 29 was the highest and the third stage, that all of the participants had morning studies, and that most of them lived in center areas. They also found that most participants had a good level of knowledge regarding the significance of breast self-examination (BSE) and how to perform it, which was a good marker for this community segment and nursing students in particular. Conclusion: The study's findings indicate that female pupils had a high degree of knowledge. Highlights: Breast self-examination (BSE) aids early breast cancer detection. Cross-sectional study; 200 female students surveyed via questionnaire. Participants showed high knowledge of BSE importance and techniques. Keywords: Female Students, Knowledge, Breast Self-Examination